2018
DOI: 10.1101/311696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A crowdsourced analysis to identifyab initiomolecular signatures predictive of susceptibility to viral infection

Abstract: Respiratory viruses are highly infectious; however, the variation of individuals' physiologic responses to viral exposure is poorly understood. Most studies examining molecular predictors of response focus on late stage predictors, typically near the time of peak symptoms.To determine whether pre-or early post-exposure factors could predict response, we conducted a community-based analysis to identify predictors of resilience or susceptibility to several respiratory viruses (H1N1, H3N2, Rhinovirus, and RSV) us… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…83 Indeed, some biological pathways and genes were identified that may confer innate susceptibility or resilience to infection. 84 Although these signatures are also relevant to the patient presenting with acute symptoms, the ability to identify an exposed but presymptomatic patient offers unique opportunities. For example, the motivation behind these human challenge studies was a Defense Advanced Research Projects Agency program called Predicting Health and Disease.…”
Section: Presymptomatic Diagnosismentioning
confidence: 99%
“…83 Indeed, some biological pathways and genes were identified that may confer innate susceptibility or resilience to infection. 84 Although these signatures are also relevant to the patient presenting with acute symptoms, the ability to identify an exposed but presymptomatic patient offers unique opportunities. For example, the motivation behind these human challenge studies was a Defense Advanced Research Projects Agency program called Predicting Health and Disease.…”
Section: Presymptomatic Diagnosismentioning
confidence: 99%